2017
DOI: 10.1186/s40886-017-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Critical Incident Reporting System (CIRS): a fundamental component of risk management in health care systems to enhance patient safety

Abstract: Background: The complexity of health care systems, the development of clinical approaches, and both scientific and technological advancements give rise to new requirements in clinical risk management. An expedient risk management is expected to deal with as many risks as possible to ensure patient safety. A prerequisite for a clinical risk management is a well-functioning error-reporting culture in health care organizations. The present study analysed the relationship between the Critical Incident Reporting Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
2
19
0
2
Order By: Relevance
“…In our review, the included studies all describe some kind of improvements based on the incidents reported, which is similar to one previous review [3] and quite different from another, in which less than half of studies reported improvements. [4] This highlights the fact that incident reporting remains an important source of input for improvements, as long as the reports provide rich qualitative data on the incident and its contexts and are analysed in a timely and professional man-ner.…”
Section: Identifying the Incidents As Input To Improvementssupporting
confidence: 68%
See 4 more Smart Citations
“…In our review, the included studies all describe some kind of improvements based on the incidents reported, which is similar to one previous review [3] and quite different from another, in which less than half of studies reported improvements. [4] This highlights the fact that incident reporting remains an important source of input for improvements, as long as the reports provide rich qualitative data on the incident and its contexts and are analysed in a timely and professional man-ner.…”
Section: Identifying the Incidents As Input To Improvementssupporting
confidence: 68%
“…The need for human factor development and better management was supported with staff training and with different technical solutions. Such improvements have also been described in previous reviews [3,4] and were supported by regular meetings and written aids or forms.…”
Section: Identifying the Incidents As Input To Improvementsmentioning
confidence: 80%
See 3 more Smart Citations